First-principles study of the electronic structure and magnetism of the element-doped SnO2 (001) surface. (April 2022) - Wang, Min; Feng, Tianlong; Ren, Jie; Gao, Leyuan; Li, Hui; Hao, Zhi; Yue, Yunliang; Zhou, Tiege; Hou, Denglu
Abstract: The electronic structure and magnetic properties of the SnO2 (001) surface doped with a nonmetal (C or N) and a transition metal (Co or Ni) were studied by first-principles calculations based on density functional theory. The pristine SnO2 (001) surface is a nonmagnetic insulator. Although the two-coordinated oxygen vacancy ( V O2c ) has the lowest formation energy, it cannot produce spin polarization on the SnO2 (001) surface, while both C and N can introduce spin-splitting defect states in the band gap. It is shown that a single C (or N) atom can produce a magnetic moment of 1.99 μ B (or 0.99 μ B ) on the surface. In addition to the local magnetic moment on the dopant atom, many spins are distributed in the crystal gap. Calculations with the generalized gradient approximation with Coulomb repulsion U show that Co (or Ni) can produce a magnetic moment of 1.0 μ B (or 2.0 μ B ) in the system, but the spin polarization occurs mainly in the valence band. Studies on magnetic coupling between dopant atoms at different distances show that only Co–Co exhibits mainly ferromagnetic coupling, while C–C, N–N, and Ni–Ni are dominated by antiferromagnetic coupling. Therefore, doping with Co can produce a relatively stable macroscopic magnetism. Graphical abstract: Image 1 Highlights: Oxygen vacancy cannot produce d 0 ferromagnetism on the SnO2 (001) surface. Both C and N can produce spin splits in the band gap on the surface. The spin polarization caused by the Co (or Ni) atom occurs in the valence band. Only Co–Co at different distances exhibits mainly ferromagnetic coupling.